Thrombocytopenia with bleeding manifestations in childhood malaria - Mohan, Kriti; Omar, B J; Singh, Rupa D; -, Aaradhana; Sachan, Ravi (Indian Journal of Child Health, 2016)
Background: Thrombocytopenia is frequently found in malaria, but its prognostic value has not been addressed in children. Bleeding with thrombocytopenia in malaria is not so common but can be a cause of mortality if left unattended. Objective: To study the occurrence and severity of thrombocytopenia with bleeding manifestations in children with malaria. Materials and Methods: This cross-sectional study was conducted in a pediatric hospital of north India. All positive cases of malaria